Sky Island : a Trot & Cap'n Bill adventure - Chu, Amy (Viking, 2020)
Trot and her cat Cap'n Bill return to help their sea siren friend Clia, who seeks their help in uncovering the kidnapping of her friend Merla. Trot's investigation leads her to a private island where an abandoned amusement park is scheduled to be redeveloped and Merla is to be the main attraction.